Patients with acute intracerebral hemorrhage and severe symptoms are highly sensitive to prehospital delay. A subgroup analysis from the RESIST and TRIAGE-STROKE trials - Behrndtz, Anne; Simonsen, Claus Z.; Valentin, Jan B.; Andersen, Grethe; Blauenfeldt, Rolf A. (Frontiers in Stroke, 2024)
Background Patients with a positive prehospital stroke severity score and underlying intracerebral hemorrhage (ICH) may be harmed by longer onset-to-admission time. We aimed to investigate the interaction between ICH severity and time from onset to admission on functional outcome. Methods This is an individual patient data analysis with data from two randomized prehospital stroke trials using the same prehospital stroke scale. Patients were stratified according to the presence of a positive stroke severity score. They were grouped into early arrivers (admitted ≤ 90 min from onset) and late arrivers (admitted ≥90 min after onset). The primary outcome was a shift toward a better functional outcome on the modified Rankin Scale (mRS). Results A total of 212 patients had ICH. A positive stroke severity score was seen in 123 of these patients. Patients with ICH and a positive prehospital stroke severity score had a significantly worse outcome if they arrived 90 min or later at the hospital (adjusted odds ratio [aOR]: 2.02, 95% CI [1.01, 4.12]). This difference was not observed in patients without a positive severity score (aOR: 0.50, 95% CI [0.22, 1.14]). Patients with a positive score also had an increased risk of death or severe dependency (mRS of 5–6) of 9.1 percentage points (95% CI [−1.6%, 19.8%]) per hour if they were diagnosed with ICH. Conclusion Longer onset-to-admission time was harmful for patients with ICH and a positive prehospital stroke severity score.